2006
DOI: 10.1038/sj.ijo.0803452
|View full text |Cite|
|
Sign up to set email alerts
|

Waist circumference and body mass index in Chinese children: cutoff values for predicting cardiovascular risk factors

Abstract: Background: Body mass index (BMI) and waist circumference (WC) correlate with cardiovascular (CV) risk factors in childhood which track into adulthood. WC provides a measure of central obesity, which has been specifically associated with CV risk factors. Reference standards for WC, and for WC and BMI risk threshold values are not established in Chinese children. Objectives: To construct reference percentile charts of WC, establish relationships between WC, BMI and other risk factors, and propose WC and BMI thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
115
2
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(141 citation statements)
references
References 53 publications
17
115
2
7
Order By: Relevance
“…Good predictors for elevated blood pressure are necessary for preventing the early onset of hypertension and its future impact on cardiovascular system. Although several anthropometric parameters have been considered to be related to cardiovascular disease (CVD) risk factors (22)(23)(24)(25), the best marker assessing the relationship between body fat and hypertension is still controversial. BMI is a well-established and widely accepted measure to define obesity in children and adolescents in spite of some limitations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Good predictors for elevated blood pressure are necessary for preventing the early onset of hypertension and its future impact on cardiovascular system. Although several anthropometric parameters have been considered to be related to cardiovascular disease (CVD) risk factors (22)(23)(24)(25), the best marker assessing the relationship between body fat and hypertension is still controversial. BMI is a well-established and widely accepted measure to define obesity in children and adolescents in spite of some limitations (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, WC has been found to be an even stronger indicator of cardiometabolic disease risk factors than BMI in children (Lee et al, 2006;Sung et al, 2007;Reinehr and Wunsch, 2010). However, a recent systematic review concluded that WC and BMI were equally useful in identifying cardiometabolic disturbances in children (Reilly et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…As described in the literature, the AC is a measurement of central obesity and it is specifically associated with risk factors of cardiovascular diseases, both in adults and children 27,28 , which makes it a relevant measurement to evaluate the risk of chronic diseases, such as hypertension. The present study showed a low prevalence of abdominal obesity.…”
mentioning
confidence: 99%